ANALISIS PEMBEBANAN TEGANGAN SISTEM PEMISAH BARANG BERDASARKAN KETINGGIAN (Science and Technology (SciTech), 2022)
Loading analysis of the prototype of the goods separator system based on the height based on this PLC, with a power supply voltage of 12 Volt DC to run the prototype system, it was found that the load that can be passed on each conveyor is a load ranging from 10-120 gr with the overall required current. 2.15 A, the required voltage is 12Vdc ± 8.99%, the time required by the system with a minimum time = 177 ms and a maximum time = 285 ms where the driver used is a 12 Volt DC motor coupled with a 5mm elastic rubber van-belt. If it exceeds the recommended load above, then there are several conveyors that cannot move due to overload, namely on the inclined conveyor with an angle of 30ᵒ, the transfer motor and the separator motor which makes the system performance less than optimal.